Pharmacodynamics of Rocuronium in Cholestatic Patients with or without Hepatocellular Injury : Normal Onset Time of Initial Dose and Prolonged Duration Time After Repeated Doses - Yang, Jian-jun; Wang, Yong-guang; Zhang, Zhuan; Zhang, Zhi-jie; Liu, Jin; Xu, Jian-guo (Journal of Pharmacy & Pharmaceutical Sciences, 2008)
Purpose. A prospective controlled study was designed to observe the pharmacodynamics of rocuronium in cholestatic patients with or without hepatocellular injury. Methods. Sixty patients undergoing abdominal surgery were allocated into three groups: group I had 20 cholestatic patients with hepatocellular injury; group II had 20 cholestatic patients without hepatocellular injury, and group III (control group) had 20 patients without hepatic disease. Anesthetized with propofol and fentanyl, all patients received rocuronium 0.6 mg/kg for initial dose followed by intermittent repeated administration of rocuronium 0.15 mg/kg. The twitch high of adductor pollicis muscle was monitored by acceleromyography. The onset time of the initial dose, the duration time of the initial and the repeated doses, and the recovery index were observed. Results. The onset and the duration time of the initial dose had no significant difference among the three groups (P>0.05). After administration of the 5th dose, the duration time of the repeated doses was significantly prolonged than that of the 2nd dose in group I(31±8 versus 22±4 min) and group II (28±5 versus 21±4 min) (P<0.05), but not in group III (P>0.05). The recovery index of rocuronium was longer in group I (48±13 min) and group II (46±9 min) than that in group III (24±5 min) (P<0.05). Conclusion. Cholestatic patients experience prolonged duration time and longer recovery index after repeated use of rocuronium, despite normal onset time after the initial dose.